Perbedaan Nilai Kadar Gula Darah Sewaktu Pada Dewasa Obesitas Dan Non ObesitasDi Kecamatan JebresKota Surakarta - Kristiyan Triani, Septa, Sigit Widyatmoko, Sp.PD.,M.Kes, dr. Safari Wahyu Jatmiko (2016)
Overweight and obesity is a health threat in most of the world's population that kills more than malnutrition. Of the 10 conditions of risk around the world, obesity is one of them and the five conditions of risk in developing countries. The prevalence of obesity increased by 9.8% in men and 11.8% in women. Obesity can cause insulin resistance that can lead to clinical manifestations in the presence of elevated levels of sugar in the blood. This situation will trigger metabolic disorders such as diabetes mellitus.This study aimed to determine the difference in value when blood sugar levels in obese and non-obese adults in KecamatanJebres Surakarta. This study is analytic observational with cross sectional approach as was conducted in Jebres Surakarta. The sample size used was as much as 79 samples in each group with consecutive sampling technique. Data obtained from the primary data.The study was conducted in the District Jebres Surakarta include Puskesmas Ngoresan, Pucang Sawit, Purwodiningrat, Sibella in January 2016. Respondents were coming and was treated with an age range of 35-65 years. The results of the analysis using Chi-Square was obtained p = 0.002 (p <0.05). Ratio prevalence figures 4.075 and Confidence Intervals 2.056 to 8.079 means that every patient obesity in adults at risk 4 times to the rise in blood sugar levels with a significant level of 5%. There is a difference in the value of blood sugar levels during the non-obese and obese adults in the District Jebres Surakarta city. Keywords: Obesity, hyperglycemia, diabetes mellitus